Estimation of soil erosion by the "Rusle" model of the Nura river basin (Journal of Geography and Environmental Management, 2021)
Over the past few decades, soil erosion has affected natural resources and agricultural production around the world. Primary soil erosion is the local impact of the influence on the decline in soil fertility and the deterioration of the quality of soil resources, while water pollution and sedimentary residues are off — site. Primary and off-site soil erosion directly affects the environment, economy, and agriculture. Excessive intensity of agriculture and anthropogenic impact leads to such problems as soil erosion. In this regard, the erosion analysis is aimed at making a characteristic of land plots according to the erosion situation for step-by-step planning in order to preserve soil and water resources near this territory. Therefore, this research topic is relevant today. To understand this situation, an erosion analysis was carried out on the example of the Nura River basin using GIS and the universal soil loss equation USLE. The purpose of this work is to determine the process of soil erosion in the Nura River basin for various types of land use. The following data were used to determine soil washout: sediment erosion potential, soil type, mechanical composition, slope steepness, vegetation, plowing types, erosion prediction model, universal Soil Loss Equation (USLE), and the ArcGIS 10.4 program. As a result of the study, the average soil washing in the Nura River basin was determined for each landfill. The percentage ratio of the A factor of the Nura River basin shows that the variation is from 0.01 to 3.15 tons / ha / year. The highest indicator for the A factor is 3.15 tons / ha / year and is characterized by the type of agriculture-arable land and mechanical composition-loamy. The lowest indicator for the A factor is 0.01 tons / ha / year and is characterized by the type of agriculture - haymaking and mechanical composition-sandy loam.  To improve the situation of the erosion potential of the Nura River basin, it is necessary to reduce the indicators of such coefficients as K - the coefficient of soil erosion and C-the coefficient of the type of crop. That is, it is necessary to improve the mechanical composition of the soil, increase soil fertility and monitor the moisture content of the soil, it is also necessary to develop the agricultural sector, engage in agriculture and raise the level of this sector. Natural factors will not give in to any changes in any way. The findings can be used as a basis for developing site-specific soil conservation plans to promote sustainable land management.
Keywords: Soil erosion, GIS, erosion analysis, Nura River basin, universal soil loss equation USLE.